Prediction of preeclampsia based on maternal serum endoglin level in women with pregestational diabetes mellitus - Roman V. Kapustin; Ekaterina V. Kopteeva; Elena N. Alekseenkova; Andrey V. Korenevsky; Ilya V. Smirnov; Olga N. Arzhanova (Hypertension in Pregnancy, 2022)
Purpose To evaluate the level of soluble endoglin (sEng) in pregnant women with pregestational diabetes mellitus (DM) and to assess its predictive value for preeclampsia development. Methods Ninety pregnant women were enrolled in the study forming five comparison groups: type 1 DM (not planned, n = 20; planned, n = 20), type 2 DM (diet, n = 15; insulin therapy, n = 20), and the control group (n = 15). The primary outcome was clinically confirmed preeclampsia. Maternal serum concentrations of sEng were measured at 11+0–13+6 and 30+0–33+6 weeks. Results sEng level was elevated in all patients with pregestational DM compared to the control group. Its plasma concentration increased with gestational age and in case of preeclampsia development. In patients with type 1 DM, serum sEng level did not depend on the presence of preeclampsia. This is evidence of severe metabolic disorder and endothelial dysfunction in these patients. The addition of sEng level to logistic models considering established risk factors (body mass index + age + HbA1c level) in the first and third trimesters significantly improved their performance for preeclampsia prediction. Conclusions Eng level may become an important marker for early prediction of preeclampsia in women with pregestational DM.